Decision trade-offs for cost-constrained fisheries management. (18th November 2015) - Little, L. Richard; Punt, André E.; Dichmont, Catherine M.; Dowling, Natalie; Smith, David C.; Fulton, Elizabeth A.; Sporcic, Miriana; Gorton, Rebecca J.
Abstract: Fisheries management operates in an environment characterized by multiple risks. These risks are often complementary and can be traded off against each other. An important goal for managers is to develop strategies to minimize the overall risk exposure at minimal cost. We show a simple model that quantifies a range of risks faced by fisheries management agencies in terms of long-term expected budgetary expenditure. The model includes not only the cost a management agency would be expected to incur from overfishing a stock, or from being seen to overfish it, but also the social cost incurred from not achieving its objectives, such as the opportunity cost of foregoing catches and economic returns. These costs can be controlled by adjusting the biomass level targeted by management, or increasing expenditures for data collection to improve the precision of biomass estimates. The overall risk, expressed as the long-term total expected cost to a management agency, depends strongly on the fisheries management objectives, and the emphasis on conservation or economic motives. In general, management under a conservation-oriented objective would reduce risk either by increasing target biomass levels or by expenditure on monitoring and assessment, while a catch-focused objective would seek to lower management costs by reducing expenditure on data collection and assessment. Increased natural stock variability affects the risk of overfishing, and long-term expected costs as the ability to make a meaningful estimate of biomass declines. Management of catch-focused fisheries would reduce the biomass target as stock variability increases, because the benefit of catches are seen to outweigh the cost, or risk of being overfished. The model provides the basis for more extensive risk analyses, and serves as a simple lesson that the consequences of reducing the short-term costs associated with managing a fishery can come with a concomitant increase in overall risk.